Accuracy and standardization of diagnostic methods for the detection of antibodies to citrullinated peptides - M. Tampoia; N. Bizzaro (PAGEPress Publications, 2011)
Anti-citrullinated peptide antibodies (ACPA) have a very high specificity for rheumatoid arthritis, much more than that of the rheumatoid factor. In addition, ACPA can be found in sera in the pre-clinical phase, are associated with more severe joint destruction and with higher disease activity. In recent years, keeping pace with new knowledge and with progress made in the antigenic composition of tests and in the characterization of immunogenic epitopes, many immunoenzymatic (ELISA) methods of second and third generation have been produced and marketed commercially, and their use has spread among clinical laboratories. Today, completely automated methods are also available, which are easy to use and with a higher throughput, rendering the diagnostic utility of testing ever faster and more effective. This review takes into consideration the more important characteristics of the new ACPA-ELISA tests now commercially available, and also considers recent progress in standardizing test results.